Les traits d’identité culturelle en lien avec le statut d’immigrant et l’ethnicité : quel lien avec les symptômes de détresse psychologique et les symptômes dépressifs dans la main-d’œuvre canadienne? Résultats des neuf cycles de l’ENSP - Kammogne, Christiane Liliane (Can J Public Health, 2019)
PURPOSE: This study investigated variations over time of psychological distress and depressive symptoms among working Canadians according to two cultural identity traits: ethnicity and immigration status. METHOD: Data came from the nine cycles of the National Population Health Survey (NPHS) conducted by Statistics Canada. Based on a sample of 7069 workers, multiple regressions analyses and multilevel regressions models were carried out. Analyses were adjusted for confounders such as age, gender, marital status, household income, social support outside the workplace, level of education, presence of children between 0 and 5 years of age and presence of children from 6 to 11 years of age. RESULTS: Over time, and after accounting for potential confounders, immigration status is not associated with psychological distress or depressive symptoms. Ethnicity is associated with depressive symptoms, but not with psychological distress symptoms. Visible minorities have less depressive symptoms compared to Caucasians. CONCLUSION: Unlike immigration status, ethnicity seems to explain a portion of mental health inequities among workers. One area to be explored in future researches is whether in the Canadian workforce, work conditions could explain ethnic inequalities in mental health.